Preparation and evaluation of Ni/CeOշ-SiOշ catalyst for dry reforming of methane with carbon dioxide in syngas production - Achmad Solichin, Sudarno (2012)
Dry reforming of methane with carbon dioxide (DRMC) has received great attention,as the process can utilize the two greenhouse gases of CH4-CO2 and produce valuable syngas. The syngas produced from this process has H2/CO = ~1, which is more compatible for various chemical and liquid fuel syntheses. However, carbon formation that leads to the catalyst deactivation is the main obstacle of DRMC process. This study is aimed to develop Ni-based catalysts with high activity, stability and high resistance to the carbon formation. This work studies the effects of different amount of promoter “ceria” loading and different preparation method of supports and catalysts. In the first study, a series of modified CeO2-SiO2 (CS) supports with different loading of ceria (CeO2) were prepared via deposition precipitation (DP). For comparison, SiO2 and CeO2 were also used as supports. The Ni (5wt.%) catalysts were synthesized using impregnation method. Several characterizations of energy dispersive X-ray fluorescence (EDXRF), N2 adsorption-desorption, X-ray diffraction (XRD), H2 temperature-programmed reduction (H2-TPR), CO2 temperature programmed desorption (CO2-TPD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and thermal gravimetric analysis (TGA) were conducted to analyze the physico-chemical properties of the prepared samples as well as to identify the carbon formation of the used catalysts. The results showed that the properties of Ni/xCS catalysts were superior to the Ni/SiO2 and Ni/CeO2 catalysts, in terms of particle sizes, Ni dispersion, reducibility and basicity. The catalytic evaluation of DRMC showed that ceria addition on the Ni-supported catalysts influenced the catalytic performances and hindered the carbon formation significantly. Among these catalysts, Ni/9CS exhibited the best properties with high catalytic performance, high stability and low carbon deposition, thus it was considered as the best catalyst with the optimal amount of ceria. For the second study, four kinds of CeO2-SiO2 (CS) supports have been synthesized via different methods, i.e. deposition precipitation (DP), Impregnation (Imp), Sol-gel (SG) and ball milling (BM). Supported Ni (5 wt.%) catalysts were also prepared via impregnation. In addition, two other catalysts, denoted as Ni/CS-DP2 and Ni/CS-D, were prepared by impregnation of CS-DP support and co-impregnation of Ni and Ce on silica with higher temperature of catalyst calcination (700 oC). The characterization results showed that the different method gave significant different physico-chemical properties, catalytic performance and coking resistant. It was found that Ni/CS-DP1 and Ni/CS-DP2 showed the excellent activity and stability, since they have good properties (morphology, reducibility and basicity as well as Ni particle size). The order of catalyst activities is Ni/CS-DP2 > Ni/CS-DP1 >Ni/CS-Imp > Ni/CS-D > Ni/CS-BM and Ni/CS-SG. However, in term of carbon deposition, Ni/CS-DP1 and Ni/CS–DP2 gave higher amount of carbon deposits than those of Ni/CS-Imp, Ni/CS-D and Ni/CS-BM. Whereas, Ni/CS-SG showed the lowest activity with the worst condition of carbon formation due to the bad properties of the catalyst.